MODEL PEMBELAJARAN ATTENTION, RELEVANCE, CONFIDENCE, SATISFACTION (ARCS) UNTUK MENINGKATKAN KEPERCAYAAN DIRI PESERTA DIDIK - Anik Oktaviani; Nurul Umamah; Marjono Marjono; Riza Afita Surya (Jurnal Pendidikan Sejarah Indonesia, 2021)
21st century skills prepare students with the knowledge and skills needed to succeed in life and careers in the world of work. One thing that needs to be developed is self-confidence which is an important character in achieving learning goals. The sample of this research is 34 students of MAN 2 Jember. The data technique used is a questionnaire. Data processing is done using SPSS. The results of the study of students' self-confidence at the pretest obtained an average score of 52.67 which indicates the category of moderate confidence and self-confidence of students at the post-test obtained an average of 81.33 which indicates that the category of high self-confidence means confidence students' self between pretest and post-test increased by 28,667. The research recommendation is that it is necessary to build a learning environment that can increase students' self-confidence. Based on the results of the study and its relationship with previous research, it shows that the ARCS learning model has an effect on increasing students' self-confidence.